Preclinical positron emission tomography imaging properties of radiolabeled nimotuzumab : a retrospective analysis towards imaging application for visualizing epidermal growth factor receptor expression - Ebenhan, Thomas (University of Pretoria, 2025)
Dissertation (MSc (Medical Nuclear Science))--University of Pretoria, 2025.